Asymmetric vowel harmony in Greenlandic fringe dialects - Rischel, Jørgen (Annual Report of the Institute of Phonetics University of Copenhagen, 1975)
This paper deals with a phenomenon characteristic of certain regional varieties of Greenlandic Eskimo, viz. the so-called "i-dialect" in which /i/ has replaced /u/ in a great many instances. It is shown that this vowel shift is due to distant assimilation, and the resultant pattern is referred to as a case of "asymmetric" vowel harmony. Various descriptive models accounting for this pattern, and their possible implications for hypotheses about internalized grammar, are discussed.